2011
DOI: 10.1021/ic201479q
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ligand-Field Parameters by Heme Ruffling in Cytochromes c Revealed by EPR Spectroscopy

Abstract: Electron paramagnetic resonance (EPR) spectra of variants of Hydrogenobacter thermophilus cytochrome c552 (Ht c-552) and Pseudomonas aeruginosa cytochrome c551 (Pa c-551) are analyzed to determine the effect of heme ruffling on ligand-field parameters. Mutations introduced at positions 13 and 22 in Ht c-552 were previously demonstrated to influence hydrogen bonding in the proximal heme pocket and to tune reduction potential (Em) over a range of 80 mV [Michel, L. V.; Ye, T.; Bowman, S. E. J.; Levin, B. D.; Hahn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(82 citation statements)
references
References 42 publications
5
76
1
Order By: Relevance
“…This analysis examined cyt c variants and demonstrated that those with the more ruffled hemes show greater rhombicity and lower g max values. [16] A similar relationship has been noted in cyanide derivatives of globins. [17] However, for a given system, the changes in g max brought about by changes in heme ruffling are relatively small, and might not account for the range of g max values observed.…”
Section: Introductionsupporting
confidence: 63%
See 2 more Smart Citations
“…This analysis examined cyt c variants and demonstrated that those with the more ruffled hemes show greater rhombicity and lower g max values. [16] A similar relationship has been noted in cyanide derivatives of globins. [17] However, for a given system, the changes in g max brought about by changes in heme ruffling are relatively small, and might not account for the range of g max values observed.…”
Section: Introductionsupporting
confidence: 63%
“…[20] Analysis of EPR spectra of cyt c variants with different amounts of heme ruffling supports the model that increasing ruffling raises the d xy orbital energy relative to that of the dp orbitals, increasing rhombicity. [16] Cyts c with more ruffled hemes are thus predicted to have more rhombic EPR spectra, corresponding to lower g max values; the observation that cyanide complexes of some globins display HALS EPR signals for species with relatively planar hemes is consistent with this finding. [17] The determination of crystal structures of Ne c-552 variants here allows us to investigate the relationship between heme conformation and electronic structure further.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…In a follow-up focused upon delineating the influence of ruf distortion vs. Fe(III)-HIS bond strength on the EPR spectra of H. thermophiles cyt c 552 and Pseudomonas aeruginosa cyt c 551 , it was again suggested that heme ruffling was correlated with decreased reduction potentials. 260 However, here the results were confounded by the fact that the reduction potentials of the mutants could also be explained by a change in the Fe(III)-HIS bond strength. However, the effects were considered separable on the basis that the observed change in the EPR axial ligand field term was opposite to what would be expected from changes in the axial HIS bond strength.…”
mentioning
confidence: 88%
“…The degree of ruffling will influence the electronic structure of the porphyrin [197,198] and has been shown to decrease delocalization of π electrons [199–205]. Inducing heme distortion by protein changes have shown that the E° can be changed by 170 mV in heme-nitric oxide/oxygen proteins [204] (Figure 16).…”
Section: Factors Affecting Redox Potentials Of Et Centers and Stramentioning
confidence: 99%